The Relationship Between Public Health Center Service Coverage and Stunting in Children Aged - Asti Dewi Rahayu Fitrianingsih; Fajria Saliha Puspita Prameswari (Universitas Pendidikan Indonesia, 2021)
According to WHO, public health problems can be considered chronic if the prevalence of stunting is more than 20%, meaning that stunting is a serious health problem in Indonesia. East Java is a province with a high prevalence of under-five and stunted nutritional status, which is 30%-40%. The Malang Regency is one of 100 priority district/city interventions. To help reduce stunting, the Puskesmas unites the growth and development of children under five and provides care to pregnant women. The purpose of this study was to determine whether there were among the puskesmas programs which included the provision of Vitamin A, the provision of blood-added tablets and the provision of additional food to pregnant women with chronic energy deficiency conditions with the incidence of stunting in Malang Regency. This research is an analytical survey research using secondary data from the Malang District Health Office. The type of sample used was purposive sampling, namely by selecting the Puskesmas with the highest stunting cases (close to 20% or more) so that 10 Public Health Center were obtained as samples and research sites. The results of the analysis showed that there was no relationship between the administration of blood-boosting tablets and the provision of additional food to pregnant women with chronic energy deficiency conditions with the incidence of stunting in Malang Regency. The importance of conducting further research on the causes of stunting in Malang Regency, caused by stunting is a complex factor, involving various factors.